Online assessment: is it too good to be true? / Ja'izah Abdul Jabar and Wan Mardyatul Miza Wan Tahir - Abdul Jabar, Ja'izah; Wan Tahir, Wan Mardyatul Miza (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Over the past few years, education has undergone a major makeover, due to COVID-19 situations. One of the big game-changers in this educational revolution has been the rise of online assessments. These days, teachers are swapping out their old-school paper exams for fancy digital tools that let them check out what students know and can do. It's not just about convenience - online assessment is making waves for all the cool things it can do. Teachers and students are totally vibing with it, and there's a lot more to it than typical pencil-and-paper tests.